The Effects of Inflation, Exchange Rates, And Gross Domestic Product on Indonesia's Crude Oil Exports - Jonatan Marbun; Armin Rahmansyah (Universitas Negeri Semarang, 2026)
This study examines the relationship between inflation, exchange rates, and Gross Domestic Product (GDP) in destination countries and Indonesia’s crude oil exports to Thailand, Malaysia, Singapore, Australia, and South Korea during 2014–2024. Using annual panel data consisting of 55 observations, panel regression analysis was conducted, with the Fixed Effect Model selected based on Chow and Hausman tests. The results indicate that inflation in destination countries is negatively and significantly associated with Indonesia’s crude oil exports. In contrast, exchange rates exhibit a negative but insignificant relationship, while GDP shows a positive but insignificant relationship with export volumes. Collectively, the three variables significantly explain 52.93% of the variation in exports. These findings suggest that macroeconomic conditions in importing countries, particularly inflation, are associated with fluctuations in Indonesia’s crude oil exports, whereas the roles of exchange rates and GDP appear limited within the observed sample. The study contributes to the trade and energy literature by providing evidence from major Asian-Pacific export destinations. However, the findings should be interpreted cautiously due to the limited number of observations and the exclusion of structural factors such as global oil prices and energy policy dynamics.